Evaluation Study on Major Development Programmes Orissa State A Study Conducted by Development Research Studies Pvt. Ltd. District Level Report Malkangiri - Planning Commission (Planning Commission, 2007)
This evaluation study examines the effectiveness of major development programmes in Malkangiri district, Orissa, including MGNREGA, PMGSY, education schemes (SSA and Ashram schools), and healthcare initiatives (ICDS and NRHM). Malkangiri, heavily forested and affected by Left Wing Extremism, exhibits high poverty levels and limited agricultural capacity, with a majority of the population comprising Scheduled Castes and Scheduled Tribes. Findings indicate widespread awareness of government schemes but low implementation efficacy: MGNREGA benefits reach only 23% of households with frequent payment delays, while PMGSY road construction is hampered by militancy-related disruptions. Education programmes have reduced illiteracy, yet teacher shortages and quality concerns persist. Healthcare access and immunization show improvement, but remoteness limits service delivery. Drinking water and sanitation infrastructure remain severely inadequate, posing critical health risks. The study concludes that persistent socio-political, infrastructural, and administrative challenges undermine programme impact, emphasizing the need for an integrated approach combining infrastructure development, effective administration, and community engagement to achieve meaningful socio-economic transformation in Malkangiri.
Submitted to Planning Commission
Submitted to Planning Commission
Keywords: Malkangiri; Rural Development; MGNREGA; PMGSY; Education Initiatives; Healthcare Services; Drinking Water; Scheduled Tribes; Poverty; Infrastructure; Programme Evaluation; Left Wing Extremism